2019
DOI: 10.1016/j.jmst.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical corrosion behaviour of Sn-Zn-xBi alloys used for miniature detonating cords

Abstract: Electrochemical corrosion behaviour of Sn-3Zn-xBi (x=0, 1, 3, 5, 7 wt.%) solder alloys were investigated using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques, to explore the effect of Bi on corrosion performance of the Sn-Zn alloy. Results indicated that minor (1 wt.%) Bi addition increased the corrosion susceptibility, mainly attributed to the coarsened and more uniformly distributed Zn-rich precipitates, while further increasing Bi decreased the corrosion susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This is consistent with the results reported by Liu et al [24]. It was found that Bi particles could act as an anodic barrier and effectively reduce the corrosion rate of Sn-Zn in 3.5 wt-% NaCl solution [25]. When In was added to Sn-9Zn, it could cause the microstructure segregation of Sn-9Zn alloy, and decrease the passive current density [26].…”
Section: Introductionsupporting
confidence: 90%
“…This is consistent with the results reported by Liu et al [24]. It was found that Bi particles could act as an anodic barrier and effectively reduce the corrosion rate of Sn-Zn in 3.5 wt-% NaCl solution [25]. When In was added to Sn-9Zn, it could cause the microstructure segregation of Sn-9Zn alloy, and decrease the passive current density [26].…”
Section: Introductionsupporting
confidence: 90%
“…It should be pointed out that the corrosion products were produced leading to further corrosion rather than protecting the bottom alloys. 29,30 With the potentiodynamic polarization curves scanning to point C, the measured potential rose sharply with an increment of current density, which was contributed to the breakdown of the corrosion product film. Due to oxygen evolution reactions, the Cl − within testing solution was absorbed into corrosion products and finally punched the nonprotective film.…”
Section: Resultsmentioning
confidence: 99%
“…Due to oxygen evolution reactions, the Cl − within testing solution was absorbed into corrosion products and finally punched the nonprotective film. 30 The detailed electrochemical parameters of studied PA6/ 6061 and CFRPA6/6061 joints in 0.5 M NaCl solution are carefully tabulated in Figure 5c and Table S4. The corrosion current density (i coor ) was gained by extrapolating the anodic Tafel region with the corrosion potential (E coor ) because of the ambiguous cathodic Tafel region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, to get a solution for that, others have concentrated on the manufacture and performance characterization of composite solders reinforced by various nanoparticles to lead-free solder alloys, while some authors have attempted to add trace alloying metals [16]. In view of that, alloying elements such as Bi [9,17], Ag, Cu [18], Ni [4,19,20], and other rare earth elements were selected as alloying additions to the Sn-Zn solder alloy in order to modify the composition. The added trace elements may form strong compounds by reaction with zinc [18], limiting its activity [21], reducing its melting point [10], and forming intermetallic compounds that enhancement the solder's mechanical properties [22].…”
Section: Introductionmentioning
confidence: 99%